Contributions of university of Ibadan botanical gardens to avifauna diversity conservation (2019)
Rapid urbanization poses the greatest threat to bird populations due to habitat loss and fragmentation. Managed habitats including nature gardens remain one of the likely areas to host displaced species and serve as secondary habitat options. This depends strongly on floristics and vegetation structure which are strong determinants of bird species distribution. This paper presents a review of bird diversity in the botanical gardens, University of Ibadan, and assesses effect of vegetation parameters on patch utilization within the garden. Point-count method and circular plots were used for bird and vegetation survey. Ten point-counts selected from the upper course and developed section of the garden were visited 37 times each, in the mornings (0630-0930 hrs) and evenings (1600- 1900hrs). Fifty-five (55) bird species belonging to 23 families were recorded. A total of 1344 plants belonging to 69 species were identified within sampling points. There was significant difference in bird richness across points (P<0.05). The patch around point 6 had the highest mean bird richness and plant abundance; showing a possible positive correlation between both factors. A significant relationship between ground cover, litter cover, canopy cover and bird species diversity was observed. Total families of plants identified were thirty-two (32) with Amaranthaceae having the highest frequency (401) while Malvaceae, Polygalaceae and Sapotaceae had the least frequency. Management practices in gardens such as introduction and re-introduction of indigenous plant species, prunning, grass clearing, can potentially affect a gardens' ability to host bird species. Proper understanding on this relationship is vital to sustaining bird populations.